Lifrarskaði tengdur notkun á Herbalife - Magnús Jóhannsson; Sif Ormarsdóttir; Sigurður Ólafsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) Objective: Many herbal products are known to be hepatotoxic. In a recent survey in Iceland concerning adverse reactions related to herbal medicines, Herbalife products were implicated in the majority of the reported cases of hepatotoxicity. Methods: The clinical presentations of five cases of Herbalife related liver injury during the period of 1999-2008 are analysed. Causality was assessed by using the WHO-UMC system for causality assessment and the RUCAM method. Results: Of the five cases there were four females and one male; median age was 46 years (range 29-78). Herbalife had been used for 1 to 7 months prior to presentation. Four patients presented with a hepatocellular and one with a cholestatic reaction. Median values were for bilirubin 190 mmol/L (range: 26-311; ref. < 20 mmol/L), ALP 407 U/L (range: 149-712; ref. 35-105 U/L) and ALT 24 87 U/L (range: 456-2637; ref. 70 and 45 U/L for males and females, respectively). Liver biopsy was performed in 2 patients and was consistent with toxic hepatitis in both cases. Other causes of hepatitis were excluded by appropriate serological testing and ultrasound. Causality assessment according to RUCAM was probable in three cases and possible in two. Using the WHO-UMC criteria causality was certain in one case, probable in two and possible in two cases. Conclusions: Hepatotoxicity is probably associated with the use of Herbalife products. Hepatotoxicity due to herbal remedies is an important differential diagnosis in the diagnostic work-up of liver injury. Tilgangur: Mörg náttúruefni eru þekkt að því að geta valdið lifrarskaða. Nýleg íslensk könnun á aukaverkunum náttúruefna sýndi að lifrarskaði var oftast tengdur notkun Herbalife. Aðferðir: Lýst er fimm tilfellum af eitrunarlifrarbólgu í tengslum við notkun á ýmsum Herbalifevörum á Íslandi á árunum 1999 til 2008. Orsakatengsl voru metin með skilmerkjum WHO-UMC en einnig með RUCAM aðferðinni. ...